Do vírus digital ao vírus real: pandemia, hiper-hibridização da vida e o binômio casa-cidade - Venancio, Leonardo Valbão (2023)
The 2020’s was marked, on a global scale, by a serious health, humanitarian and economic crisis due to the new class of viral respiratory disease caused by Covid-19 (SARS-CoV-2). There is a sudden disruption of everyday reality at different levels and a forced rearrangement of human relationships.The center of the reflections presented revolves around the tensions generated in the architectural environment, notably in the housecity binomial. This problem will be analyzed from the perspective of territorialization processes, considering that, with the pandemic, the city is the environment that is deterritorialized and the house the space of abrupt reterritorialization. Under the territorialization process, the improvisation process will also be highlighted, centered on materiality and action, which reinforced Brazilian socioeconomic, housing and urban disparities during the pandemic. It is important to emphasize the aggressive insertion of digital media as mediators of reality, a central theme of the debate throughout the work, which through the real/virtual hyper-hybridization of life influence the experience and perception of architecture and urbanism, themes worked on the production of presence and production of ambience in the house-city binomial. The role of this research has at its core recording and reflecting on how the pandemic has become a culmination of change in contemporary society, and which, based on the presence and omnipresence of technology, impact on the production of the home-city binomial today. Conditioned to the digital propagation that left the house towards the city after the quarantine (constant and naturalized surveillance and metaverse, for example), the aim is finally to discuss the biocapitalist and biopolitical ties that the pandemic has reinforced.